Perbandingan Metode Analytical Hierarchy Process (AHP) dan Himpunan Keanggotaan Fuzzy pada Penilaian Kinerja Dosen - Noni Namida Oliviani; Haris Rafi; Mochammad Febri Hariyadi; Nova El Maidah (Faculty of Computer Science, University of Jember, 2018)
Utilization of artificial intelligence has been imposed into many things, one of them on the assessment of lecturer's performance, one of them on the lecturer's performance assessment. Artificial intelligence can help and facilitate a person to solve a particular problem. In general, the purpose of lecturer performance assessment is to determine the best lecturer's order through predetermined criteria. Decision Making Method (AHP) and Function Membership Fuzzy is a method often used to determine lecturer performance assessment. There is a method that is a form of calculation whose output is the value of several lecturers who entered the assessment list. The purpose of the comparison is to know which artificial intelligence method is best applied to the lecturer's performance assessment. The method used to test the artificial intelligence applied to the lecturer's performance assessment is to use a comparison scenario. Based on the analysis that has been done, the result that artificial intelligence using AHP method and Membership Sets Fuzzy have balanced result. Based on the document can be concluded that in this study AHP method is a superior method in terms of accuracy, while the Fuzzy method is superior in terms of effectiveness.